Administration duration influences the effects of low‐magnitude, high‐frequency vibration on ovariectomized rat bone. Issue 7 (28th December 2015) - Qing, Fangzhu; Xie, Pengfei; Liem, Yacincha Selushia; Chen, Ying; Chen, Xuening; Zhu, Xiangdong; Fan, Yujiang; Yang, Xiao; Zhang, Xingdong
ABSTRACT: Low‐magnitude, high‐frequency vibration (LMHFV) has been proposed as a non‐drug anti‐osteoporosis treatment. However, the influence of administration duration on its effect is seldom investigated. In this study, the effect of 16‐week LMHFV (0.3 g, 30 Hz, 20 min/day) on the bone mineral densities (BMDs), bone mechanical properties, and cellular responses of osteoporotic and healthy rats was examined by in vivo peripheral quantitative computed tomography (pQCT), fracture tests, cell assays, and mRNA quantification. Forty‐eight adult rats were equally assigned to sham surgery (SHM), sham surgery with LMHFV (SHM+V), ovariectomy (OVX), and ovariectomy with LMHFV (OVX+V) groups. At week 8, LMHFV ameliorated ovariectomy‐induced deterioration of trabecular bone, with a significantly higher tibia trabecular BMD (+11.2%) being noted in OVX+V rats (vs. OVX). However, this positive effect was not observed at later time points. Furthermore, 16 weeks of LMHFV caused significant reductions in the vertebral mean BMD (−13.0%), trabecular BMD (−15.7%), and maximum load (−21.5%) in OVX+V rats (vs. OVX). Osteoblasts derived from osteoporotic rat bone explants showed elevated BSP and OSX mRNA expression induced by LMHFV on day 1. However, no further positive effect on osteoblastic mRNA expression, alkaline phosphatase activity, or calcium deposition was observed with prolonged culture time. A higher ratio of RANKL/OPG induced by LMHFV suggests that osteoclastogenesis may be activated. Together, these results demonstrate that administration duration played an important role in the effect of LMHFV. Early exposure to LMHFV can positively modulate osteoporotic bone and osteoblasts; however, the beneficial effect seems not to persist over time. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1147–1157, 2016.